The Effectiveness of Inductive and Deductive Strategies to Improve Motivation and Achievement in Learning Science of Junior High School Students - Allesius Maryanto (Journal of Science Education Research, 2019)
This study aimed to determine the effectiveness of teaching using the inductive and deductive strategies on the improvement of learning achievement and motivation students. This study was a quasi-experimental study, involved all students of class IX of SMPN 2 Sentolo, Kulonprogo in the academic year of 2010/2011. Sample was established using the purposive sampling technique, two science classes each of 32 students were taught using the inductive and deductive strategy. The data were gathered  using a pretest and posttest. The students’ achievement was measured using a multiple choice test and their motivation were measured using a questionnaire and observation sheets. The results show that: (1) there is a difference of science instruction through deductive and inductive strategies on improving learning achievement, which is supported by Independent Samples Test in the t-test column for Equality of Means, score value of sig. (2 tailed) is 0,026; (2) there is no differences of deductive and inductive strategies on improving students’ motivation, which is supported by t-test column for Equality of Means, score value of sig. (2 tailed) is 0,153; (3) there is a significant correlation of motivation on learning science and science achievement, which is shown by the value of coefficient of correlation 0,736.